Mononuclear and Terminal Zirconium and Hafnium Methylidenes1. Issue 41 (11th August 2014) - Kamitani, Masahiro; Pinter, Balazs; Chen, Chun‐Hsing; Pink, Maren; Mindiola, Daniel J.
Abstract The dimethyl aryloxide complexes [(PNP)M(CH3)2(OAr)] (M=Zr or Hf; PNP−=N[2‐P(CHMe2)2‐4‐methylphenyl]2); Ar=2, 6‐iPr2C6H3), which were readily prepared from [(PNP)M(CH3)3] by alcoholysis with HOAr, undergo photolytically induced α‐hydrogen abstraction to cleanly produce complexes [(PNP)M=CH2(OAr)] with terminal methylidene ligands. These unique systems have been fully characterized, including the determination of a solid‐state structure in the case of M=Zr.